Islamic values in the culture of Chinese Kazakhs (Journal of Philosophy Culture and Political Science, 2018)
One of the pressing problems of today – the condition and culture and Islamic religion of Kazakh Diaspora in the People’s Republic of China, which is part of the global community of Kazakhs. To understand the culture of the Kazakh people need to learn and understand the socio-political and religious situation of the Kazakh Diaspora.This article provides a brief historical analysis of the spread of Islam and its influence on the culture and way of life among the Kazakh Diaspora in ChinaKey words: Islam, religion, culture, East Turkestan, China.